9t+8=10t

Simple and best practice solution for 9t+8=10t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t+8=10t equation:


Simplifying
9t + 8 = 10t

Reorder the terms:
8 + 9t = 10t

Solving
8 + 9t = 10t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-10t' to each side of the equation.
8 + 9t + -10t = 10t + -10t

Combine like terms: 9t + -10t = -1t
8 + -1t = 10t + -10t

Combine like terms: 10t + -10t = 0
8 + -1t = 0

Add '-8' to each side of the equation.
8 + -8 + -1t = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -1t = 0 + -8
-1t = 0 + -8

Combine like terms: 0 + -8 = -8
-1t = -8

Divide each side by '-1'.
t = 8

Simplifying
t = 8

See similar equations:

| 10h+2h-8h=16 | | -7x+5=-12+4 | | -n^2+16n-34=-4n^2+1 | | 6=9(3+7f) | | -2(q+9)=2 | | 3/8=a/8 | | -5p+17=-18 | | 4(3x-1)=5x+6 | | 4/15-2/3 | | (x/2)-15=125 | | 2z-2x+2y+2z^3=0 | | -.75x+6=-12 | | 1h+7=17 | | v(x)=(12-2x)(16-2x)(x) | | 10k-11k=20 | | 0x+2y+2z=0 | | -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 | | y=2+13y | | 20x+y=180 | | 12x+6x^2=9x^2 | | 2(5x+3)=x+6(x+1) | | 7y+3x=58 | | -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 |

Equations solver categories